Effectiveness of Public Health Services at Jongaya Health Center Makassar City - Nurrahmah, Lutfiah; Haedar Akib; Herman H (Universitas Negeri Makassar, 2026)
This study aims to identify and describe the level of effectiveness of health services provided by the Jongaya Health Center in Makassar City along with supporting and inhibiting factors. The type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results of the study indicate that in terms of time, the service at the Jongaya Health Center is quite good. This can be indicated by the patient waiting time which is still within reasonable limits, although it can be longer when the number of patients increases. In addition, employees generally arrive on time, although some are late, but this delay does not interfere with the smoothness of the service. The duration of service per patient is also quite effective, depending on the type of service provided. In terms of accuracy, the service has been running well. This can be indicated by the thoroughness of medical personnel in the initial examination and administration of medication. Errors in administering medication rarely occur, and if there is an error, it is immediately corrected. The public also considers that the service is quite accurate, although there are complaints about the waiting time. In terms of service style, employees have provided friendly and professional service. This can be demonstrated by clear communication, the suitability of services to patient needs, and good interaction between employees and patients. Although the conditions of crowded interactions can feel faster, patients still feel flattered. Supporting factors related to the effectiveness of health services at the Jongaya Health Center in Makassar City are good. This is demonstrated by the existence of routine training for employees to improve skills and cooperation with various health institutions that expand access to services. Meanwhile, inhibiting factors are still not optimal. This is manifested by the existence of obstacles that interfere with employees, such as the attitude of impatient patients, technical problems, and the process of procuring medical devices that require permits and budget limitations.